2022
DOI: 10.1038/s41524-022-00853-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of organic superionic glassy conductors by process and materials informatics with lossless graph database

Abstract: Data-driven material exploration is a ground-breaking research style; however, daily experimental results are difficult to record, analyze, and share. We report a data platform that losslessly describes the relationships of structures, properties, and processes as graphs in electronic laboratory notebooks. As a model project, organic superionic glassy conductors were explored by recording over 500 different experiments. Automated data analysis revealed the essential factors for a remarkable room temperature io… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A property graph database can be a powerful tool because connections, such as those representing the varied relationships between structures, properties, and processes in materials exploration, can be easily seen. 143 Visualization of graph databases is often used when there are large amounts of variables with many complex possible connections, as is the case in the different synthetic and processing conditions of silica aerogels and the relationship of those conditions to aerogel properties. To understand the influence of aerogel synthetic and processing variables, we developed the silica aerogel graph database (SiAGDB).…”
Section: Overview Of Aerogel Synthesis and Processingmentioning
confidence: 99%
“…A property graph database can be a powerful tool because connections, such as those representing the varied relationships between structures, properties, and processes in materials exploration, can be easily seen. 143 Visualization of graph databases is often used when there are large amounts of variables with many complex possible connections, as is the case in the different synthetic and processing conditions of silica aerogels and the relationship of those conditions to aerogel properties. To understand the influence of aerogel synthetic and processing variables, we developed the silica aerogel graph database (SiAGDB).…”
Section: Overview Of Aerogel Synthesis and Processingmentioning
confidence: 99%
“…[1][2][3] Unlike human researchers, computers can obtain an overview of huge material structure databases and extract universal trends. New photoluminescent compounds, 4 solar cell components, 5 battery electrolytes, 6,7 and energy-related materials have been extracted through data science. 3,[8][9][10][11][12][13] In silico material screening is expected to accelerate research cycles and also is compatible with automated experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using charge-transfer (CT) polymer materials as battery electrolytes was first introduced in the patent literature . The three-part combination of polymer with electron-donating groups, small-molecule organic electron acceptors, and salt was reported to achieve surprisingly high ionic conductivity (10 –4 S/cm at room temperature). , Later, Oyaizu and co-workers reported that an array of small-molecule charge-transfer complexes mixed with lithium salt also exhibited elevated ionic conductivity (10 –6 to 10 –4 S/cm at room temperature) . The authors hypothesized that fast ion transport occurs at the interfaces between the charge-transfer crystals and salt.…”
mentioning
confidence: 99%